ANALISIS KINERJA, NILAI TAMBAH DAN MITIGASI RISIKO RANTAI PASOK AGROINDUSTRI BAWANG MERAH - Ayu Resti Pamungkassari, Marimin, dan Indah Yuliasih (Jurnal Teknologi Industri Pertanian, 2018)
The supply chain of shallot agroindustry is in urgent situation owing to theimbalance risk and added-value distribution of the actors in the supply chain. The purposes of this research were (1) to identify the mechanism and performance of shallot supply chain; (2) to measure the added-value of supply chain actors; (3) to identify and mitigate the risk in shallot supply chain; and (4) to select the strategy to improve the performances, added-value, and risk mitigation ofshallot supply chain. Supply Chain Operations Reference-Analytical Hierarchy Process (SCOR-AHP)wereemployed to measure the performance of shallot supply chain.Hayami method was used to analyze the added-value.House of Risk (HOR)was used to identify and mitigate the risk, while the strategies for the improvements were formulated using Analytic Network Process-Benefit Opportunity Cost Risk analysis (ANP-BOCR) method. Analysis on the supply chain performance showed those classified as below average were farmer (75.38%), first collector (74.43%), and industry (74.79%), whereasthe second collector hadagood performance (91.97%). Added-value ratios were for the industry of 53.75%, farmer of 46.06%, first collector of 8.88%, and second collector of 5.39%.Total effectivity measurement of risk mitigation to prioritized risk agent resulted the farmer had11 preventive actions,the collectors had9 and the industry had8. The supply chain evaluation resulted in four alternatives for the improvement strategy of the performance, added-value and risk mitigation.The best alternative with the highest BO/CR ratio was the implementation of the SOP of proper cultivation and post-harvesting method.Keywords: shallot agroindustry, risk mitigation, supply chain, value added